Character Education in Christian Religious Education - Duha, Terasa; Rogate Artaida Tiarasi Gultom; Dapot Damanik (Tinta Emas Institute, 2025)
Character education is a very important aspect in the educational process, especially in the context of Christian Religious Education. Christian Religious Education not only aims to provide knowledge about religious teachings, but also to shape the character of students in accordance with noble Christian values. Values ​​such as love, honesty, simplicity, and a sense of responsibility are the basis for building good character and can be applied in everyday life. Therefore, teaching Christian Religious Education needs to integrate moral and ethical learning in every teaching material. In this study, the role of Christian Religious Education in shaping the character of students is discussed, as well as strategies that can be applied in character education based on Christian teachings. Christian religious education not only teaches the teachings of the Christian faith, but also educates students to develop characters in accordance with the teachings of the Bible. The concept of character education involves teaching about love, honesty, humility, hard work, and mutual respect. Through the integration of Christian teachings and moral values ​​taught in the educational process, it is hoped that students can build attitudes and behaviors that reflect a strong Christian identity. In this context, educators act as role models who provide a positive influence on the development of students' character. Thus, character education in Christian religious education becomes an important foundation in forming individuals who are not only intellectually intelligent, but also emotionally and spiritually mature, and able to contribute positively to society.